Co-evolved plant and blast fungus ascorbate oxidases orchestrate the redox state of host apoplast to modulate rice immunity - Hu, Jiexiong; Liu, Muxing; Zhang, Ao; Dai, Ying; Chen, Weizhong; Chen, Fang; Wang, Wenya; Shen, Danyu; Telebanco-Yanoria, Mary Jeanie; Ren, Bin; Zhang, Haifeng; Zhou, Huanbin; et al. (Elsevier, 2022)
Apoplastic ascorbate oxidases (AOs) play a critical role in reactive oxygen species (ROS)-mediated innate host immunity by regulating the apoplast redox state. To date, little is known about how apoplastic effectors of the rice blast fungus Magnaporthe oryzae modulate the apoplast redox state of rice to subvert plant immunity. In this study, we demonstrated that M. oryzae MoAo1 is an AO that plays a role in virulence by modulating the apoplast redox status of rice cells. We showed that MoAo1 inhibits the activity of rice OsAO3 and OsAO4, which also regulate the apoplast redox status and plant immunity. In addition, we found that MoAo1, OsAO3, and OsAO4 all exhibit polymorphic variations whose varied interactions orchestrate pathogen virulence and rice immunity. Taken together, our results reveal a critical role for extracellular redox enzymes during rice blast infection and shed light on the importance of the apoplast redox state and its regulation in plant-pathogen interactions.